Microbial Fermentation Affects the Structure–Activity Relationship of Bioactive Compounds in Ginseng and Its Applications in Fermentation Products: A Review - Juan Bai; Zixian Zhu; Wei Luo; Miran Jang; Beibei Pan; Ying Zhu; Jiayan Zhang; Yansheng Zhao; Xiang Xiao (Foods, 2025)
Microbial fermentation technology has emerged as a pivotal approach for enhancing ginseng efficacy through the transformation of active ingredient molecular structures. This paper reviews the impact of microbial fermentation on the structure–activity relationship of ginseng bioactive compounds and advances in its application. Bibliometric analysis indicates that Panax species (Panax ginseng, Panax notoginseng) are primarily fermented using lactic acid bacteria and Aspergillus spp., with research predominantly focused on conversion efficiency to rare ginsenosides (Compound K, Rg3, and Rh2). Specifically, this review details the biotransformation pathways of these rare ginsenosides and the resultant bioactivity enhancements. Additionally, it summarizes the effects of other microorganisms, such as fungal fruiting bodies, on additional ginseng constituents like polysaccharides and polyphenols. Microbial fermentation has been successfully implemented in functional products, including ginseng vinegar, wine, and fermented milk. This review subsequently examines these applications, emphasizing fermentation’s potential to enhance product functionality. However, challenges remain in strain screening, process standardization, and analysis of multi-component synergistic mechanisms. In summary, this review synthesizes recent advancements in understanding the mechanisms of microbial fermentation on ginseng and its translational applications in functional foods and pharmaceuticals.